'Social distancing' during COVID-19: the metaphors and politics of pandemic response in India. Issue 2 (3rd May 2020) - Rahman, Sabina Yasmin
ABSTRACT: In the wake of the COVID-19 pandemic, public health authorities in India presented a contradictory picture between their role in assisting the state to mitigate the global crisis and dealing coercively with the needs of its diverse populations. Conventionally, public health is viewed as an evidence-based profession that is above politics. Yet national responses to COVID-19 in India reveal the embeddedness of health and illnesses in the larger politics of the state. Although it is still early to assess the full spectrum of damage caused by lack of central-level planning, this article argues against COVID-19 being viewed as a 'great leveller'. Rather, it suggests that we inhabit somatic societies that regularly employ the vocabulary of pathology/disease to determine social health. Moreover, the Indian experience illustrates how, even during a pandemic, 'social distancing' is not an apolitical notion. It becomes a measure for the state to co-opt scientific interventions of risk mitigation and relay them to people as a metaphor for exclusion: thereby exacerbating deeper structural inequities around which access to health and well-being of the population is organised.